Clean and Healthy Life Behavior in the View of the Prophet's Hadith - Fajar Ramadhan; Casram Casram (Gunung Djati Conference Series, 2021)
This study aims to discuss the behavior of clean and healthy living according to the view of the hadith. This research is a qualitative type by applying a literature study to interpret the hadith about clean and healthy living behavior with a content analysis approach. The results and discussion of this study include clean and healthy living behavior, hadith of clean and healthy living behavior, and experience of clean and healthy living behavior. This study concludes that humans are the most noble creatures created by Allah Swt than other creatures by being given physical gifts, reason, and lust. For this reason, man is the only creature that is very perfect, physically he can do various things, then with his mind he can think and solve a problem and finally with his lust he can have a strong desire. Healthy desire is something that is coveted by all humans. Of course, before having the desire to be healthy, humans need to pay attention to themselves and the surrounding environment, basically awareness of cleanliness is what makes humans able to live comfortably and of course health can be guaranteed.